Identificação molecular e caracterização de peixes do gênero Zungaro (Siluriformes: Pimelodidae) de diferentes bacias hidrográficas - Pires, Antonio Augusto Adami (Universidade Federal de São Carlos, 2014)
The Genus Zungaro, Bleeker, 1858 (Siluriformes: Pimelodidae), comprise a group called Jaú. This group is divided in two species: Zungaro jahu located in Paraná- Paraguai basins and Zungaro zungaro located in Amazonas-Orinoco basins. Both species are known because they are the biggest catfish in South America. In Juruena River, smaller catfishes are found by local fishermen and because of that it´s very hard to classify these species. During this work Juruena population was genetically analyzed and these molecular datum were compared with other population to know if they are the same specie or not. Samples of fish came from Juruena, Amazonas, Solimões, Madeira, Xingu, Meta, Miranda, Taquari e Cuiabá were collected and kept in the heap of tissue bank in the Molecular Biodiversity and Conservation Laboratory (LabBMC). After isolating the DNA according to Sambrook protocol, mitochondrial sequences of cytochrome oxidase I (COI), cytochrome b (Cytb) and D-Loop were amplified by PCR. After the sequencing and edition, the results were compared to the databases BOLD and GenBank. Phylogenetic trees based on different algorithms were built. The species of Amazonas-Orinoco basins (Z. zungaro) and Paraná-Paraguai basins (Z. jahu) showed a considerable genetic distance highlighting a population structuring. Individual from Juruena River were different from the others following the model K2p 2.4% (COI) and 5% (D-Loop). The results showing an evidence of three different species: Z. zungaro, Z. jahu and possible new species in the Juruena River. Besides, specimens from Xingu River demonstrated a high genetic distance from the others, being necessary further analyses.
Keywords: Peixe; Filogeografia; Identificação molecular; Zungaro; Distribuição geográfica; Rio Juruena; Filogenia; Juruena river; Molecular identification; Phylogeny; CIENCIAS BIOLOGICAS::GENETICA